13q- syndrome. Family study. Issue 12 (December 1977) - Carmichael, A; Addy, D P; Shortland-Webb, W R; Cameron, A H; Davies, I C
Abstract : A patient is described who had a deletion involving the long arm of chromosome number 13. The mother and 4 of 7 living sibs showed a balanced translocation from the long arm of a number 13 chromosome to the long arm of a number 3 chromosome. We stress the importance of investigating the families of children with chromosomal defects.